Human relations : principles and practices - Reece, Barry L.; Brandt, Rhonda (Boston, MA : Houghton Mifflin, 2000)
Introduction to human relations. Improving interpersonal communications. Building high self-esteem. Personal values influence ethical choices. Attitudes can shape your life...
Keywords: Career development; Interpersonal relations; Career development